2022
DOI: 10.4314/ejhs.v32i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Social support and meaning of life in women with breast cancer

Abstract: BACKGROUND: Social support is known as an affection-oriented coping mechanism when a person is involved with cancer. Therefore, this study was conducted to investigate the relationship between family social support and the meaning of life in women with breast cancer.METHODS: In this cross-sectional study, 84 women with a mean age of 60 (SD = 5.7) years with breast cancer who were admitted to a teaching hospital participated. Data were collected using social support and meaning of life questionnaires. After col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…In this study, the median social support score of older adult homebound breast cancer patients was 34 (moderate), lower than previously reported survey points (39.35 ± 9.51) ( Jadidi and Ameri, 2022 ). This may be related to the fact that hospitalization and home care for breast cancer patients require more support and companionship from family members.…”
Section: Discussioncontrasting
confidence: 86%
“…In this study, the median social support score of older adult homebound breast cancer patients was 34 (moderate), lower than previously reported survey points (39.35 ± 9.51) ( Jadidi and Ameri, 2022 ). This may be related to the fact that hospitalization and home care for breast cancer patients require more support and companionship from family members.…”
Section: Discussioncontrasting
confidence: 86%
“…A national wide survey among Chinese adults also showed a negative associations between lifestyle scores and loneliness [ 34 ]. The reason why lonely individuals are easier to have a poor healthy lifestyle may be related with their poor self-motivation, low spiritual growth, insufficient social support and increased social isolation [ 35 37 ]. Previous studies reported that patients with schizophrenia engage less in and make limited use of community resources and had a poorer social relationship [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have explored the association between HL and spiritual well-being in different populations, such as maternal HL among women ( Khorasani et al ., 2022 ), or patients living with kidney disease (undergoing haemodialysis) ( Hassani et al ., 2022 ). Moreover, earlier research has emphasised the need to increase social support to promote spiritual issues, specifically, the meaning of life among women with breast cancer ( Jadidi and Ameri, 2022 ). However, the findings from these earlier studies are inconsistent and not generalisable to women experiencing homelessness.…”
Section: Discussionmentioning
confidence: 99%